2009
DOI: 10.1017/s0021900200006057
|View full text |Cite
|
Sign up to set email alerts
|

Tail Dependence for Heavy-Tailed Scale Mixtures of Multivariate Distributions

Abstract: The tail dependence of multivariate distributions is frequently studied via the tool of copulas. This paper develops a general method, which is based on multivariate regular variation, to evaluate the tail dependence of heavy-tailed scale mixtures of multivariate distributions, whose copulas are not explicitly accessible. Tractable formulas for tail dependence parameters are derived, and a sufficient condition under which the parameters are monotone with respect to the heavy-tail index is obtained. The multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…It was shown in [14] that tail dependence functions {b * S (w i , i ∈ S; C S )} and the exponent function a * (w; C) are uniquely determined from one to another. In fact, the detailed relations between the intensity measure µ and tail dependence function b * have been established in [19], and in particular,…”
Section: Bounds For Tail Risks Via Tail Dependence Functionsmentioning
confidence: 99%
“…It was shown in [14] that tail dependence functions {b * S (w i , i ∈ S; C S )} and the exponent function a * (w; C) are uniquely determined from one to another. In fact, the detailed relations between the intensity measure µ and tail dependence function b * have been established in [19], and in particular,…”
Section: Bounds For Tail Risks Via Tail Dependence Functionsmentioning
confidence: 99%
“…Schmidt [27] showed that bivariate elliptical distributions possess the tail dependence property if the tail of their generating random variable is regularly varying. The explicit expressions of the orthant tail dependence for multivariate Marshall-Olkin distributions have been derived in [17], and the moment-based formulas for multivariate tail dependence of scale mixtures of multivariate distributions, such as multivariate t-distributions, have been established in [3,18]. The use of (1.5) to study the contagion risk among 25 European and US banks is reported in [6].…”
Section: Theorem 11 a Distribution G Is An Mev Distribution With Stmentioning
confidence: 99%
“…and [31,18,25] further studied the properties of the tail dependence function and their applications for multivariate t copulas, vine copulas and heavy-tailed scale mixtures of multivariate distributions, respectively. We refer to the above papers for details and properties of tail dependence functions.…”
Section: Introductionmentioning
confidence: 99%